Home-cage behavior is impacted by stress exposure in rats - Eraslan, Evren; Castelhano-Carlos, Magda João; Amorim, Liliana; Soares-Cunha, Carina; Rodrigues, Ana João; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2023)
Being social animals, rats exhibit a range of social behaviors which help them to build social bonds and maintain group cohesion. Behavior is influenced by multiple factors, including stress exposure and the expression of the impact of stress effects in both social and non-social behaviors may also be affected by the living conditions of rats. Here, we explored the physiological and behavioral effects of chronic unpredictable stress on rats that were group-housed in the PhenoWorld (PhW), a socially and physically enriched environment closer to real-life conditions. Data confirms that stress exposed triggers anxiety-like behavior. In terms of home-cage behaviors, we found that stress affects social behaviors (by decreased playing and increasing huddling behaviors) as well as non-social behaviors (as shown by decreases in rearing and walking behaviors). These results are of relevance to expand our knowledge on the influence of stress on social and non-social behaviors which are of importance to understand better species-typical behaviors.